Pozzolanic and Cementing Activity of Raw and Pyro-Processed Saudi Arabian Red Mud (RM) Waste - Pavia, Sara; Alelweet, Omar; Lei, Zehao (My University, 2021)
This paper investigates the composition, properties and reactivity of a red mud waste generated in Saudi Arabia with a view to find alternative materials to replace construction binders of high environmental impact. The phase transformation triggered by the sintering of the RM up to 1000°C is determined with thermal and X-Ray Diffraction analyses. Reactivity is investigated with chemical and physical methods including the Chapelle test, setting times, mechanical index and microscopy. The RM is clearly pozzolanic, and its activity is mainly due to the reaction of feldespathoids and the formation of zeolitic and feldspathoid-based hydrates. The positive effects of the thermal treatment are seen below 750°C, and include the loss of water in the zeolite/feldespathoids, and the destruction of the crystal structures of the clay minerals inherited form the parent bauxite. The negative effects of the thermal treatment are evidenced over 750°C, with a decrease in specific surface area, devitrification and crystal formation, whereby the active transition aluminas and the fedespathoids/zeolites (mainly cancrinite) transform into nepheline, tricalcium aluminate (C3A) and gehlenite. Despite the occurrence of nepheline, C3A and gehlenite in the RM sintered at 1000°C, the formation of pozzolanic hydrates that cause setting and strength development are greater at lower temperature. The optimum thermal treatment that enhances pozzolanic activity lies at c.400°C, as evidenced by the highest lime combination, the greatest mechanical index and the fastest set. The RM consists of gibbsite and boehmite, inherited from the bauxite, and cancrinite, chantalite and sodalite formed during the Bayer process. Feldespathoids have formed, instead of zeolites, due to the available silica and the high alkali content of the RM. The quick lime -CaO -, added twice during the refining process, has transformed the original goethite into hematite, and produced cancrinite. The Saudi RM has high SiO2 and high alkalinity, and an abundant specific surface area available for reaction. The chloride and carbon contents are low, and no environmental toxicity is inferred from its chemistry.
PUBLISHED
Keywords: Red mud; Pozzolanic activity; Thermal activation; Zeolites; Feldspathoids